Originally Posted by

**Educated** Simplify: 4(3-x) / x-3

(I don't know if this is correct or not)

Suppose that it is an equation, with an equals:

$\displaystyle y=\dfrac{4(3-x)}{x-3}$

$\displaystyle -1 * y=-1 * \dfrac{4(3-x)}{x-3}$

$\displaystyle -1y=\dfrac{4(x-3)}{x-3}$

$\displaystyle -1y=4$

$\displaystyle y=-4$

$\displaystyle \dfrac{4(3-x)}{x-3} = -4, x\ne{3}$

It has lost some data when it is simplified to -4, because x cannot be 3.

Is the second simplify question:

$\displaystyle \dfrac{x+13}{x^3(3-x)} * \dfrac{x(x-3)}{5}$ ?

And the forth one:

$\displaystyle \dfrac{x-4}{\frac{x}{4}-\frac{4}{x}}$ ?